Work Discipline and Job Satisfaction as the Influencing Factors that Increase the Employee's Performance - Astuti, Widi; Nagatirta, Partama; Luwiha, Luwiha; Purwandoko, Edi; Andriyaningsih, Ayu (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2023)
This study aims to determine the effect of work discipline and job satisfaction on employee performance. Severe and essential element in a company to manage employees is not so easy because every employee has different characteristics and other factors to improve their performance. Likewise, PT Putra Bali also expects an increase in employee performance to achieve optimal company goals. This study used a quantitative descriptive method; the population was 130 permanent employees at PT Putra Bali in the city of Bandar Lampung. The technique for sampling in this study used a saturated sampling technique. This study processed the data using the SPSS version 25 application to obtain significant results. The results of multiple regression testing show that the variables of Work Discipline and Job Satisfaction positively affect Employee Performance based on the results of the regression equation and with the value of R Square. Based on statistical data, the indicators in this study are valid, and the variables are reliable. Hypothesis testing using the t-test shows that the variables of Work Discipline and Job Satisfaction are proven to affect the Employee Performance variable significantly. Then through the F test, it can be seen that the variables of Work Discipline and Job Satisfaction simultaneously influence employee performance variables with the result that the calculated F value is greater than the F table.